Methods for measuring 1/1 error field in Wendelstein 7-X stellarator. (3rd June 2016) - Bozhenkov, S.A.; Lazerson, S.; Otte, M.; Gates, D.A.; Sunn Pedersen, T.; Wolf, R.C.
Abstract: Wendelstein 7-X is an optimized helical axis stellarator that came into operation at the end of 2015. A m / n   =  5/5 island chain is used in most of its configurations to form a divertor. This island chain at ι = 1 is sensitive to symmetry-breaking error fields, with the resonant 1/1 field being of particular concern because of its influence on the divertor heat flux distribution. Measurement and compensation of the 1/1 mode is therefore necessary. Experimentally, vacuum error fields in W7-X will be studied with a flux surface mapping diagnostic. In this paper numerical simulations for planning and analysing such measurements are presented. Two methods for determining the 1/1 mode are considered: measurement of the island width and measurement of a helical shift of the magnetic axis. Measurement of the resonant island width is a sensitive technique, but the island structure is also affected by other co-resonant components. A complementary method is to measure a helical shift of the magnetic axis in a configuration close to the resonance. This method has a simple interpretation and isolates the 1/1 error field from higher order resonant modes.